2018
DOI: 10.1111/jpc.13805
|View full text |Cite
|
Sign up to set email alerts
|

Normocytic Normochromic Anaemia and Asymptomatic Neutropenia in a 40‐Day‐Old Infant Breastfed by an Epileptic Mother Treated With Lamotrigine: Infant's Adverse Drug Reaction

Abstract: in 24-48 h.2 Although our case regained consciousness within 2 h, the course went probably this way. In a study in which complete recovery was the endpoint, two HBO sessions were shown to have worse outcomes than one session in patients with initial coma. 3 Our case suggests the contrary. Repeated HBO therapy could have allowed the oedema to resolve, as in delayed encephalopathy.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The UAR serves as a metric to identify outlying infants with exposure as demonstrated using the infant predicted 95th percentile in AUC ∞ . To date, adverse effects were observed in three breastfed infants (12,16, and 40 day olds) from mothers who were taking lamotrigine (38,49,55). In this study, the presented UARs demonstrated that lamotrigine exposure through breastfeeding can reach levels similar to those in mothers taking 200 mg, although the probability is likely to be low.…”
Section: Discussionmentioning
confidence: 63%
“…The UAR serves as a metric to identify outlying infants with exposure as demonstrated using the infant predicted 95th percentile in AUC ∞ . To date, adverse effects were observed in three breastfed infants (12,16, and 40 day olds) from mothers who were taking lamotrigine (38,49,55). In this study, the presented UARs demonstrated that lamotrigine exposure through breastfeeding can reach levels similar to those in mothers taking 200 mg, although the probability is likely to be low.…”
Section: Discussionmentioning
confidence: 63%
“…Adverse effects of breastfeeding have rarely been reported. However, there is one case report of episodes of apnea in a breastfed infant [38] and one case of anemia at 40 days after birth, which normalized after stopping breastfeeding [39].…”
Section: Lamotriginementioning
confidence: 99%
“…Based on 92 published cases, the lamotrigine milk/maternal serum concentration ratios have ranged from 0.18 to 1.4, with averages in most studies in the order of 0.6 to 0.7 [29][30][31][32][33][34]. Infant/maternal serum concentration ratios were reported in 166 mother-child pairs, and ranged from 0.2 to 0.9, with a reported average in individual studies in most cases at around 0.3 [29][30][31][32][34][35][36][37][38][39]. Adverse effects of breastfeeding have rarely been reported.…”
Section: Lamotriginementioning
confidence: 99%
“…On the other hand, there are case reports of serious adverse effects in breastfed infants attributed to pharmacological treatment of the mother [ 4 , 5 ], which is why a careful risk-benefit evaluation must be performed for each medicine.…”
Section: Introductionmentioning
confidence: 99%